Three-dimensional finite element analysis of reinforced concrete columns with FRP and/or steel confinement. (15th August 2015) - Teng, J.G.; Xiao, Q.G.; Yu, T.; Lam, L.
Highlights: A 3D finite element approach for circular confined concrete columns is presented. The proposed approach is based on an accurate plastic-damage model for concrete. The accuracy of the approach is demonstrated using available test results. The confinement mechanism of steel bar-confined RC columns is examined. Abstract: The strength and ductility of reinforced concrete (RC) columns can be substantially enhanced though lateral confinement which may be provided by transverse steel reinforcement and/or a supplemental fiber-reinforced polymer (FRP) jacket. Despite extensive past research on confined concrete columns, most of the existing work has been either experimental or empirical, particularly when discrete steel hoops/spirals need to be considered. This paper instead is focused on the alternative approach of three-dimensional (3D) finite element (FE) analysis of circular FRP-confined RC columns, with the discrete nature of transverse steel reinforcement properly captured. The key to the success of such FE analysis lies in an accurate constitutive model for the concrete which is under 3D compressive stresses, and this is achieved in the present study by building on an accurate plastic-damage model recently proposed by the authors' group. In implementing this plastic-damage model, a "local" stress–strain model for concrete under uniform confinement, obtained by resolving a number of issues associated with 3D FE modeling, is employed to generate data for the input parameters. The proposed FE approach is capable of providing accurate prediction for both FRP-confined RC columns and steel-confined RC columns as demonstrated through comparisons with existing test data. FE results obtained for steel-confined circular RC columns are also examined in detail to gain an improved understanding of the confinement mechanisms in these columns.